Zn finger proteins: Key ways for metalloregulation - Gven, Mzehher; Gven, Hseyin; Karataş, Fikret; Aygn, A. Denizmen; Bektaş, Srr (My University, 2002)
Zinc finger proteins have become one of the most intriguing and interesting targets in biological and medical studies. In recent years some studies have provided new approaches in the manipulation of zinc finger-dependent processes, such as development, tumor, and inflammatory diseases. Paradoxically, those unique properties of this extensive family of proteins depend on metal-binding characteristics, which might be an interesting link between standard approaches to gene therapy and metalloregulation by a numerous intracellular events. This review summarizes some recent achievements in this area of studies. © 2002 Wiley-Liss, Inc.
Keywords: NF-kappa B; Sp1; Transition metals; Zn finger proteins